Implementasi Assesmen Autentik pada Pembelajaran Al-Qur’an Hadist - Farisa Rahmadani; Febriana Putri; Fitriani Fitriani; Hani Fadilah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
Learning Al-Qur’an and Hadith in secondary schools is still largely influenced by traditional assessment practices that prioritize written examinations and memorization, which are insufficient to capture students’ actual competencies. This situation often leads to less meaningful learning and limits the development of students’ deep understanding and Islamic character. In essence, Al-Qur’an and Hadith education is intended not only to ensure mastery of theoretical content but also to encourage the internalization and application of Islamic values in everyday life. For this reason, authentic assessment is viewed as a suitable approach because it evaluates learning outcomes in a more comprehensive manner, covering cognitive, affective, and psychomotor aspects. This study aims to analyze the implementation of authentic assessment in Al-Qur’an and Hadith learning at the secondary school level and to examine its effectiveness in improving students’ understanding and learning engagement. The research employed a quantitative method, with data collected through a Google Form questionnaire distributed to students and analyzed using descriptive analysis. The results demonstrate that authentic assessment contributes to deeper conceptual understanding, enhances practical skills such as proper Qur’anic recitation based on tajwid rules and hadith memorization, and promotes active, confident, and responsible learning attitudes. Overall, authentic assessment provides more meaningful learning experiences and represents an effective alternative assessment strategy to improve the quality of Al-Qur’an and Hadith learning in secondary schools.